PERANCANGAN SISTEM KEAMANAN RUMAH BERBASIS IoT DENGAN NodeMCU ESP8266 MENGGUNAKAN SENSOR PIR HC-SR501 DAN SENSOR SMOKE DETECTOR - M. Reza Hidayat; Christiono Christiono; Budi Septiana Sapudin (Sekolah Tinggi Teknik - PLN, 2018)
Along with the development of science and technology, problems often occur that threaten security at home. These problems originate from a level of security that does not meet security standards at home. Various problems that can threaten home security conditions are fire hazards that can be caused by neglect of home temperature regulation and electrochemical equipment that is uncontrolled by the homeowner or thief danger that can easily enter the house. The design of the home security system prototype is programmed and controlled by the NodeMCU ESP-8266 to transmit all data from sensor readings to the interface on the Cayenne dashboard. PIR sensor (HC-SR501) has a digital output, if the sensor detects a movement, the NodeMCU ESP-8266 will give a logical value of one. Gas sensor concentration (MQ-02) in testing has an average difference of 2.79 ppm (part per million). The reading results of all sensors will be measured through the Internet of Things interface displayed on the Cayenne dashboard, the simulated gas concentration with gas matches with the difference results, test results and analysis results of 2.79 ppm (part per million) and if the gas sensor (MQ -02) Exceeds the specified parameters, the buzzer will sound. PIR sensor testing (HC-SR501) will work optimally by human movement if at an angle of 45˚ because the success rate is 100% in ten experiments and in the 90˚ angle the success rate is 80%.